1999
DOI: 10.1143/jjap.38.5922
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Modeling of Electron Transport and Capture Processes in AlGaAs/GaAs Multiple Quantum Well Infrared Photodetectors

Abstract: The results of an ensemble Monte Carlo (MC) particle modeling of vertical electron transport and capture processes in AlGaAs/GaAs multiple quantum well infrared photodetectors (QWIPs) are presented. The MC model employed takes into account features of the conduction band structure, the electron scattering parameters, and the interaction (reflection, transmission and capture) of free electrons with the QWs. It is shown that the heating of free electrons and their redistribution over the conduction band valleys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…As can be seen from eqs. (16) and (18), the amplitude of the periodic electric-field structure increases with receding from the threshold. Equations (18) and (20) show that the formation of periodic electric-field domains and the increase in their amplitude with increasing donor concentration lead to a sublinear dependence of the photocurrent on this concentration.…”
Section: Periodic Domainsmentioning
confidence: 93%
See 2 more Smart Citations
“…As can be seen from eqs. (16) and (18), the amplitude of the periodic electric-field structure increases with receding from the threshold. Equations (18) and (20) show that the formation of periodic electric-field domains and the increase in their amplitude with increasing donor concentration lead to a sublinear dependence of the photocurrent on this concentration.…”
Section: Periodic Domainsmentioning
confidence: 93%
“…24 and references therein) and in MC simulations. 16,17) However, the electric-field dependence of the capture rate and, consequently, the capture parameter become complex when the electric field is not uniform. It was assumed in phenomenological models of the electron transport in multiple QW structures 9,11,14,15) that the capture rate into a QW is determined by an active field which, in turn, is determined by the electric fields at both sides of this QW.…”
Section: Equations Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Monte-Carlo simulation method has been widely used to calculate the electron transport in semiconductor devices [11][12][13][14][15]. In this method, sets of random numbers are used to execute the simulation in order to determine the type of the scattering phenomena that can be expected in semiconductor materials etc.…”
Section: Monte-carlo Methodsmentioning
confidence: 99%
“…1 Several physical models using both analytical and numerical simulation approaches have been proposed for steady-state and transient operation of QWIP's. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Early models of QWIP's with multiple QW's assumed that the electric-field distribution in the active region is uniform. 12,13 Later, it has been shown that the space charge gives rise to the nonuniformity of the electric field either near the emitter contact 15,17,[19][20][21] or spread across the whole structure.…”
Section: Introductionmentioning
confidence: 99%